One hundred and eighty days of Aprismo - Humala Tasso, Ulises (2007)
After the first 100 days of the second government of Dr. Alan García and following a rite, which is wanted to be democratic and republican, driven largely by the powerful media, very few could avoid evaluating the beginnings of this APRA government.